2014
DOI: 10.1093/eurheartj/ehu101
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of idiopathic giant cell myocarditis and cardiac sarcoidosis by myocardial gene expression profiling

Abstract: Myocardial gene expression profiling is a reliable method to predict the presence of multinuclear giant cells in the myocardium, even without a direct histological proof, in single small EMB sections, and thus to reduce the risk of sampling errors. This profiling also facilitates the discrimination between IGCM and CS, as two different clinical entities that require immediate and tailored differential therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 24 publications
0
42
0
2
Order By: Relevance
“…5 At least 1 study has found that GCM and CS have distinct gene expression profiles that can be used to distinguish between them; genetic profiling may represent a promising future ancillary testing option. 28 Fulminant lymphocytic myocarditis can present similarly to GCM with new-onset heart failure unresponsive to standard therapies such as diuretics, b-adrenergic blocking agents, and angiotensin-converting enzyme inhibitors. 29 Histologically, both fulminant lymphocytic myocarditis and GCM show a myocardial lymphocytic infiltrate with associated myocyte necrosis.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…5 At least 1 study has found that GCM and CS have distinct gene expression profiles that can be used to distinguish between them; genetic profiling may represent a promising future ancillary testing option. 28 Fulminant lymphocytic myocarditis can present similarly to GCM with new-onset heart failure unresponsive to standard therapies such as diuretics, b-adrenergic blocking agents, and angiotensin-converting enzyme inhibitors. 29 Histologically, both fulminant lymphocytic myocarditis and GCM show a myocardial lymphocytic infiltrate with associated myocyte necrosis.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In the case of GCM there is no distinctive clinical presentation, but, as for other forms of myocarditis, GCM can present as acute or chronic heart failure, arrhythmia, myocardial necrosis with normal coronary arteries, or a life-threatening condition (cardiac arrest or carcinogenic shock). Some clinical hints are the severity of cardiac symptoms, the lack of response to standard cardiological care and the association in the patient or in family members with other extra-cardiac autoimmune conditions, such as autoimmune thyroid disease, ulcerative colitis, etc [10][11][12]. It is reported that GCM has a relationship with an auto immune diseases such as Sjogren's syndrome, giant cell arteritis, thymoma, myasthenia gravis, chronic active hepatitis, Hashiomoto's thyroiditis, ulcerative colitis and Crohn's disease [2,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…This allows the identification of specific disease situations by analyzing of neighbouring biopsies [75] [76]. Diagnosis of complex diseases by only one parameter is quite difficult hence current diagnostic biomarker panels are consisting of only few deregulated genes.…”
Section: Biomarker Based Diagnostics For Personalized Medicinementioning
confidence: 99%
“…The identification and differentiation of IGCM and CS, two fatal myocardial diseases, is rather difficult and based on differential patterns of inflammatory cell infiltration and non-caseating granuloma. Since both multinuclear giant cells and granuloma are easily missed by conventional histological evaluation, an improved method to reliably identify those entities independent from histology is desirable [75] [76]. In this respect, the application of diagnostic gene expression profiling can predict multinucleated giant cells without their direct histological proof and thus differentiate IGCM from CS, active myocarditis or an inflammation-free myocardium [75].…”
Section: Biomarker Based Diagnostics For Personalized Medicinementioning
confidence: 99%
See 1 more Smart Citation